The Effect of Statutory Sick Pay Regulations on Workers' Health - Martin Halla; Susanne Pech; Martina Zweimüller (Institute for the Study of Labor (IZA), 2015)
Social insurance programs typically comprise sick leave insurance. An important policy parameter is how the cost of sick leave are shared between workers, firms, and the social security system. We show that this sharing rule affects not only absence behavior, but also workers' subsequent health. To inform our empirical analysis we propose a simple model, where workers' absence decision is taken conditional on the sharing rule, health, and a dismissal probability. Our empirical analysis is based on high-quality administrative data sources from Austria. Identification is guaranteed by idiosyncratic variation in the sharing rule (caused by different policy reforms and sharp discontinuities at certain tenure levels and firm sizes). An increase in either the workers' or the firms' cost share (both at the public expense) decrease the number of sick leave days. Variations in the workers' cost are quantitatively more important (by a factor of about two). Policy-induced variation in sick leave has a significant effect on subsequent health (care cost). The average worker in our sample is in the domain of presenteeism, i.e. an increase in sick leave (due to reductions in the workers' or the firms' cost share) would reduce health care cost.
Keywords: I18; J22; J38; 330; statutory sick-pay regulations; sick leave; presenteeism; absenteeism; moral hazard; health care cost